Nano Composite Fe-Co-V /Zeolite as a Nano Carrier for Folic Acid Drug Controlled Release - Shima Zangeneh Yousef Abadi; Mohammad Kazem Mohammadi; Haman Tavakkoli (Shiraz University of Medical Sciences, 2021)
large reserves of zeolites has been one of the comparative advantages of the country in this field and provides economic justification for its use in a variety of applications, including medical and pharmaceutical fields such as artificial kidney manufacturing, wound dressing, controlled drug release, and bone tissue engineering. In order to protect the drug folic acid (folate) in digestive system acidic environments, zeolite nano carrier (Fe-Co-V/zeolite) was used. After dissolving in ethanol, a certain amount of this drug was placed on zeolite and extracted at different time periods. The release rate of folic acid in similar conditions of stomach and intestine was measured by placing samples of zeolite containing this compound in aqueous solution with an acidic pH of 5.4 and 8.9. The release rate in acidic medium was 17% more than the release of drug in alkaline medium. SEM test was performed to measure the morphology of the pores and to measure the changes in the acidic grade to evaluate the buffering properties of this material. According to the findings of this study, folic acid is very unstable in acidic conditions and use of zeolite, significantly protected the folic acid. This can be attributed to the nature of automatic control of the acidic degree in the tolerable range of the drug (chemical protection). It is also important to note that the highly porous structure of zeolite can affect the initial absorption as well as the release of desired amount of vitamins in an area of chemical protection.